A major plant practice report in Del Monte Philippines, Inc. Bugo, Cagayan de Oro City Philippines - Ladera, Jelyn Gallardo (2006)
Del Monte Philippines, Inc. located at Bugo, Cagayan de Oro City gave the author the opportunity to apply the theories and principles she learned from course under the Food Technology degree program. The author accomplished the minimum number of hours required by the curriculum which is 288. During the whole duration of the practicum, she was exposed to the operations of Liquid Processing department to truly understand the technologies and methods involved in fruit juice production. The plant practice took place from April 10-May 19, 2006
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2006
Keywords: Pineapple; Canned pineapple